Evaluation of optic nerve head parameters, retinal nerve fiber layer and macular thickness in metabolic syndrome - Mat Min, Faridah (2015)

(untitled)
TITLE Evaluation of optic nerve head parameters, retinal nerve fiber layer, and macular thickness in metabolic syndrome INTRODUCTION Metabolic Syndrome (MetS) denotes a common cluster of naturally connected risk factors including obesity, elevated blood pressure, insulin resistance, dyslipidaemia, proinflammatory state and prothrombotic state. This systemic risk factor are proved to have influence on microcirculation and blood flow autoregulation of the optic nerve head (ONH). The recent availability of retinal imaging such as optical coherence tomography (OCT) play an important role to differentiate the appearance of optic nerve head (ONH), retinal nerve fiber layer (RNFL) and macular thickness and therefor can be used for macular and optic nerve analysis. OBJECTIVES This study aim is to evaluate ONH parameters, RNFL and macular thickness using RTVue-100 Fourier domain OCT in MetS and Non-MetS group among Hospital Sultanah Nur Zahirah (HSNZ) staffs METHODOLOGY A comparative cross sectional study was carried out from Mac 2013 till October 2014 in Hospital Sultanah Nur Zahirah. A total of 230 eyes was included in this study (one eye from each of 230 subjects) in which 77 eye from MetS and 156 eye from Non-MetS group and were compared between this groups. All subjects underwent ophthalmologic examination including visual acuity, anterior and posterior segment examination. An assessment of ONH parameters, RNFL and macular thickness in 4 quadrant was conducted using RTVue-100 OCT. RESULTS: The result showed MetS group generally have higher value of ONH parameters as compared to Non-MetS group with exception of two ONH parameters; disc area and rim area. Meanwhile for the RNFL parameter thickness generally showed thinner mean value in MetS group. However there were no statistically significant difference seen between MetS and Non-MetS for both parameters. Whereas macular parameter thickness result showed MetS group had thicker mean value compared to Non-MetS group with exception of inferior hemisphere, superior and inferior quadrant of parafovea subareas. More specifically, macular thickness were significantly thicker in MetS than Non-MetS in the temporal quadrant of parafoveal, 304.45(16.61); 293.88(18.82) with p value <0.001, inferior hemisphere of perifovea 288.10(23.62); 280.09(22.25) with p value 0.013 and temporal quadrants of perifovea 289.57(21.85); 277.23(21.90) with p value <0.001. CONCLUSION: MetS significantly affect macular thickness at the temporal part of parafovea area, temporal and inferior hemisphere of perifovea area, but not affect the ONH parameters and RNFL.